Wybrane aspekty bezpieczeństwa danych w systemach informatycznych - Ziora, Leszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The aim of this article is to present classification of threats of Information Systems and directions of their protections. The article defines the notion of data security and explains such terms within the scope of data security as modification, destruction, copying, confidentiality, inviolability of data. The paper presents also international standards of security classes. The research results included in the article come from reports elaborated by CERT Poland, iDefense and Symantec enterprise. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 112-121